2020
DOI: 10.1111/hepr.13544
|View full text |Cite
|
Sign up to set email alerts
|

Is platelet monitoring during 7‐day lusutrombopag treatment necessary in chronic liver disease patients with thrombocytopenia undergoing planned invasive procedures? A phase IIIb open‐label study

Abstract: Aim: Lusutrombopag is approved for thrombocytopenia in chronic liver disease patients planned to undergo invasive procedures. In previous clinical studies, lusutrombopag treatment was stopped in patients with an increase in platelet count (PC) of ≥20×10 9 /L from baseline and whose PC was ≥50×10 9 /L (discontinuation criteria). We assessed the influence of platelet monitoring during lusutrombopag treatment in lusutrombopag naïve patients. Methods: In this open label study, Child-Pugh class A and B (A/B) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In the phase 1/2 study, the analysis of variance for class A, B, and C patients, including CP class as a fixed effect, was performed for the following pharmacokinetic parameters: the ln-transformed values for C max , AUC 0– τ , λ z , t 1/2, z , and CL/F. For this analysis, Child–Pugh class A and B patients were included from the open-label, phase 3b study (1338M0633) [ 14 ]. The ratios of the geometric least squares means and the corresponding 90% confidence intervals (CIs) were estimated by exponentiating the differences in means and the corresponding 90% CIs in the logarithm.…”
Section: Methodsmentioning
confidence: 99%
“…In the phase 1/2 study, the analysis of variance for class A, B, and C patients, including CP class as a fixed effect, was performed for the following pharmacokinetic parameters: the ln-transformed values for C max , AUC 0– τ , λ z , t 1/2, z , and CL/F. For this analysis, Child–Pugh class A and B patients were included from the open-label, phase 3b study (1338M0633) [ 14 ]. The ratios of the geometric least squares means and the corresponding 90% confidence intervals (CIs) were estimated by exponentiating the differences in means and the corresponding 90% CIs in the logarithm.…”
Section: Methodsmentioning
confidence: 99%
“…To prevent the potential risk of thrombosis due to an excessive increase in platelets after the administration of lusutrombopag, the dose-stopping rule was implemented for avoiding platelet-overshooting in the L-PLUS 1 and L-PLUS 2 studies. As an inference result of the previous studies, it is possible that there is little difference in the probability of PLT higher than 200 × 10 9 /L without the dose-stopping rule in the course of seven-day treatment of lusutrombopag, and monitoring of platelet in patients administered lusutrombopag was not necessary [26]. This study further confirmed the conclusion that the risk of platelet counts exceeding 200 × 10 9 /L with a fixed seven-day dosing regimen is low, and additional platelet monitoring is not needed during the administration of lusutrombopag.…”
Section: Discussionmentioning
confidence: 90%
“…41 In a phase 3b study of lusutrombopag in patients with Child-Pugh class A or B CLD, patients receiving a second cycle of lusutrombopag (n = 8) had increased platelet counts similar to those of patients receiving the first cycle (n = 94). 61 In a study of lusutrombopag in 14 patients with cirrhosis, there was no significant difference in the rate of platelet count increase between the first, second, and third or later treatment cycles (p = 0.87). 62 Other studies on repeated lusutrombopag treatment in a small number of patients have reported an increase in the platelet count after the second treatment cycle that was similar to that after the first treatment cycle.…”
Section: Retreatment With Tporasmentioning
confidence: 95%